Behavioural and Organizational Dynamics of Farmer Producer Organizations in India: A Review of Genesis, Traits and Challenges - Badigi Pavan Naik; Mahamaya Prasad Nayak; Indira Priyadarsini Pattnaik; Srabani Ghosal (Archives of Current Research International, 2025)
Farmer Producer Organizations (FPOs) have emerged as transformative institutions aimed at improving the socio-economic resilience and market access of small and marginal farmers in India. This review synthesizes findings from 47 peer-reviewed studies to explore how behavioural determinants—such as innovativeness, decision-making, risk-bearing ability, achievement and economic motivation, business and communication skills, feedback usage, and credit-seeking behaviour—influence the functioning and sustainability of FPOs. Anchored in behavioural theories such as the Theory of Planned Behaviour, Social Identity Theory, and Social Learning Theory, the paper emphasizes the role of socio-psychological factors in shaping farmer engagement and organizational outcomes. The review also documents institutional challenges including credit constraints, governance issues, and infrastructural deficits that hinder the optimal performance of FPOs. By bridging empirical evidence with theoretical insights, the study offers a holistic perspective on how behaviour-centric approaches can enhance FPO effectiveness, informing policy design, capacity-building interventions, and extension strategies tailored to rural India’s evolving agricultural landscape.